2011
DOI: 10.1590/s1519-69842011000300010
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of bioaugmentation in the removal of organic matter in aquaculture systems

Abstract: Several techniques are currently used to treat effluents. Bioaugmentation is a new bioremediation strategy and has been employed to improve effluent quality by treating the water during the production process. This technology consists basically of the addition of microorganisms able to degrade or remove polluting compounds, especially organic matter and nutrients. The objective of this study was to assess the effects of bioaugmentation on some parameters of organic matter and on the performance of juvenile til… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Ada tiga jenis bakteri menguntungkan yang digunakan dalam budidaya adalah bakteri yang dapat menjaga kualitas air, seperti bakteri nitrifikasi (Liu et al 2016;Brown et al 2013). Yang kedua adalah bakteri untuk bioaugmentasi yang terlibat dalam menghilangkan polutan organik dari air (Ferreira et al 2017;Lopes et al 2011). Yang ketiga adalah probiotik untuk hewan budidaya (Akhter et al 2015;Egerton et al 2018).…”
Section: Studi Makroalga Sebagai Biofilter Terhadap Pertumbuhan Dan S...unclassified
“…Ada tiga jenis bakteri menguntungkan yang digunakan dalam budidaya adalah bakteri yang dapat menjaga kualitas air, seperti bakteri nitrifikasi (Liu et al 2016;Brown et al 2013). Yang kedua adalah bakteri untuk bioaugmentasi yang terlibat dalam menghilangkan polutan organik dari air (Ferreira et al 2017;Lopes et al 2011). Yang ketiga adalah probiotik untuk hewan budidaya (Akhter et al 2015;Egerton et al 2018).…”
Section: Studi Makroalga Sebagai Biofilter Terhadap Pertumbuhan Dan S...unclassified
“…For aquaculture, little is known regarding the interactions between antimicrobials, water quality and microbial communities in brackish fish culture ponds. Bacteria that can decompose organic pollutants in the culture water can be used as beneficial bacteria for aquaculture [34][35][36]. Study of Chang et al (2019) demonstrated that the addition of sulfamethoxazole (SMX) decreased the abundance of ammonia-oxidizing bacteria (AOB), nitrite-oxidizing bacteria (NOB) and photosynthetic bacteria in milkfish culture ponds.…”
Section: Introductionmentioning
confidence: 99%
“…The first are bacteria that can maintain water quality, such as nitrifying bacteria [6,7]. The second are bacteria for bioaugmentation that are involved in the removal of organic pollutants from water [8][9][10]. The third are gut probiotics for cultured animals [11,12].…”
Section: Introductionmentioning
confidence: 99%